Use of gatekeeper in obese patients with fecal incontinence before bariatric surgery, is it improving the results? - Ibrahim, Ahmed Abdel Monem (International Surgery Journal, 2017)
Background: Fecal incontinence or bowel incontinence is a lack of defecation control with loss of bowel continent for gas, liquid, or solid content. Causes of incontinence are so different and might occur as apart of diarrhea or constipation. After following up patients with gastric bypass surgery for bariatric purpose we observe that most of them develop incontinence by different grades after bariatric surgery. Also, some of them complaining from soiling by different degrees before any operative procedure. Gatekeeper is a bulking agent recently introduced for treatment of fecal incontinence, implants of polyacrylonitrile (4-6) implants are inserted in inter-sphincteric space (Gatekeeper, THD) is used as a bulking agent to increase the volume in the inter-sphincteric space in cases of fecal incontinence follow-up was at 2, 4, 8 months. Aim is to evaluate efficacy of gatekeeper application in obese patient with fecal incontinence after bypass bariatric surgery. Methods: Thirty obese patients (19 females) and (11 males) undergoing bariatric surgery at Alsalama Hospital Abu Dhabi from the period between July 2015 to July 2017, are classified into two groups (group I) 15 patients (9 females and 6 males) are subjected to gatekeeper before gastric bypass surgeries and (group II) 15 patients (10 females and 5 males) not subjected to the use of gatekeeper and both groups were followed at 2, 4 and 8 months postoperative. Results: This randomized controlled study was conducted on 30 patients between July 2015 to July 2017 at Alsalama hospital Abu Dhabi. The use of gatekeeper in obese patients undergo bypass surgery is un effective technique to improve liquid stool incontinence. Conclusions: The use of gatekeeper in obese patients with fecal incontinence before gastric bypass surgery has improved the incontinence postoperative signs and symptoms.